THE EFFECT OF PROBLEM BASED LEARNING ON STUDENTS’ RECOUNT TEXT WRITING ACHIEVEMENT - Dyan Yosephin Hutagalung; Lince Sihombing; Elia Masa Gintings (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2015)
This research deals with the effect of problem based learning on students’ recount text writing achievement. The population of this research was the students of  VIII SMP of SMP Negeri 18 Medan in Academic Year 2015 / 2016. This research was conducted with two randomized groups namely experimental group and control group. The experimental group was taught by using problem based learning strategy and the control group was taught without using problem based learning. The researcher collected the data by giving essay test in the written test form. In order to know the reliability of the test, the researcher used inter-rater formula. The result of the reliability was 0, 93. The data was analyzed by using t-test formula. The analysis showed that the mean scores of the students in the experimental group was significantly higher than the mean scores of the students in the control group at the level of significant α= 0.05 with the degree of freedom (df) 70 with tobserved value 7,327 > ttable value 1,994. Therefore, null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The finding indicated that problem based learning  significantly affected the students’ achievement in writing recount text. Key words: Problem Based Learning, Recount Text, Writing Achievement